The growth of sheep I. – General characterisation of meat production: A review - Kupai, Tímea; Lengyel, Attila (Acta Agraria Kaposváriensis, 2005)
The understanding of growth and development of muscle is one of the most important goals in meat science. In this part the prenatal and postnatal changes in tissue-types, chemical composition and conformation were studied. The major determinants of the volume of lamb are the number and the size of constituent muscle fibres. The growth of lean tissue is composed of hyperplasia during prenatal and hypertrophy during postnatal life. The adipose tissue plays an important role as well, especially in meat quality. The reviewed process and influenced factors determined the end of keeping in order to product economically.
Keywords: sheep; growth; lean; fat; composition; conformation